Infectious Threats, the Intestinal Barrier, and Its Trojan Horse: Dysbiosis - Iacob, Simona; Iacob, Diana Gabriela (Frontiers in Microbiology, 2019)
The ecosystem of the gut microbiota consists of diverse intestinal species with multiple metabolic and immunologic activities and is closely connected with the intestinal epithelia and mucosal immune response, with which it builds a complex barrier against intestinal pathogenic bacteria. Any quantitative or functional changes of intestinal microbiota, referred to as dysbiosis, alter the immune response, destabilize intestinal homeostasis and decrease epithelial permeability. Consequently, the excessive overgrowth of pathobionts (Staphylococcus, Pseudomonas, E.Coli) favours intestinal translocations with gram negative bacteria or their endotoxins and could further trigger sepsis, septic shock, secondary peritonitis or various intestinal infections. Intestinal infections also induce epithelial lesions and perpetuate the risk of translocation and dysbiosis through epithelial ischemia and pro-inflammatory cytokines. Furthermore, the decline of protective anaerobic bacteria (Bifidobacterium, Lactobacillus) and the inadequate release of immune modulators such as butyrate affects the release of antimicrobial peptides, de-represses microbial virulence factors and alters the innate immune response. As a result, intestinal germs represent a common etiology of infections in immunosuppressed patients, infants and elderly patients and digestive tract infections are a common pathology of HIV-positive patients. Antibiotic or antiretroviral treatments also promote intestinal dysbiosis, followed by the selection of resistant germs which could later become a source of infections. The current article addresses the strong correlations between the intestinal barrier and microbiota and the role of dysbiosis in destabilizing the intestinal barrier and promoting infectious disease.